PESANTREN AS A FORMATIVE INSTITUTION FOR INTELLECTUAL AND MORAL DEVELOPMENT OF SANTRI FOR INDONESIA'S DEVELOPMENT - Indra, Hasbi; Alim, Akhmad (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: This study explores the role of pesantren (Islamic boarding schools) as formative institutions in the intellectual and moral development of santri (students) in Indonesia. Purpose: The research emphasizes the significance of pesantren in fostering not only religious knowledge but also critical thinking and ethical values among santri, preparing them to contribute meaningfully to national development. Method: Utilizing a qualitative approach, the study involves interviews, observations, and document analysis to assess the educational practices within pesantren, focusing on their curriculum, teaching methods, and community engagement. Result: The findings reveal that pesantren play a crucial role in shaping the character and competencies of santri, equipping them with the necessary skills to address contemporary societal challenges. Moreover, the study highlights the potential of pesantren in reinforcing Indonesia's human capital development through a holistic education system that integrates spiritual, moral, and intellectual growth. Conclusion: Overall, this research underscores the importance of pesantren in supporting Indonesia's progress by nurturing well-rounded and responsible individuals.